Different microbiological profiles between hip and knee prosthetic joint infections. (22nd May 2019) - Tsai, Yifang; Chang, Chih-Hsiang; Lin, Yu-Chih; Lee, Sheng-Hsun; Hsieh, Pang-Hsin; Chang, Yuhan
Purpose: The study aims to analyze the demographics and microbiological profiles of hip and knee prosthetic joint infection (PJI) and to compare the microbiological differences between hip and knee PJI. Methods: We performed a retrospective study of all PJI cases between January 2006 and December 2014 at a referral medical center in Taiwan. Results: A total of 294 PJI cases were collected: 159 were identified as hip PJI and 135 as knee PJI. The most common causative pathogen was Staphylococcus aureus (78 cases, 27%), followed by coagulase-negative staphylococci (CoNS, 42 cases, 14%). Methicillin-resistant staphylococci (MRS) accounted for 21% of all PJI cases. Fungus and mycobacterium were only involved in 12 cases (4.1%) of all PJI cases. Polymicrobial pathogens, anaerobes, and enteric gram-negative bacilli (GNB) were more likely to occur in hip joint prostheses than in knee joint prostheses (22 vs. 6 cases, p = 0.006; 11 vs. 0 cases; p = 0.002; 20 vs. 6 cases; p = 0.014, respectively). Conclusion: The prevalence of polymicrobial pathogens, anaerobes, and enteric GNB was higher in the prosthetic hip infection than in the prosthetic knee infection. The high prevalence of MRS, including Methicillin-resistant (MR) S. aureus and MR-CoNS in PJI, may warrant the need for empiric antibiotic therapy with broader coverage while pending the culture result of PJI. Although fungal and mycobacterial PJI cases are rare, the incidence of these infections is relatively high in Taiwan. Fungus and mycobacterium should also be taken into consideration whenever a persistent PJI case is encountered.